Kinetics of Corrosion of Copper Metal in Presence of Benzoic Acid Derivatives - M. El-Kashlan, Howaida (Asian Journal of Chemistry, 2011)
The rate of copper corrosion in presence of phosphoric acid were studied using weight loss method and by measuring the anodic limiting current in case of anodic corrosion. The rate of corrosion is measured in presence and in absence of benzoic acid, p-toluic acid, phthalic acid and salicylic acid. The factors studied are types of organic acid and its concentration, concentration of H3PO4, viscosity of solution, density, diffusion coefficient and the rate of rotation. In presence of these acids, it has been found that the rate of corrosion and anodic corrosion decrease. The percentage inhibition ranged from 9.72-60.14 % in case of anodic dissolution and from 9.62- 65.38 in case of weight loss method. Flory-Huggery kinetic isotherm was applied. It is found that, the rate of corrosion decreases in order salicylic acid > phthalic acid > p-toluic acid > benzoic acid. The rate of corrosion depends on phosphoric acid concentration and electrode height. Increasing the speed of rotating electrode was found to increase the rate of corrosion. The dimensionless groups were calculated for the different acids.